The Effect of Contextual Teaching and Learning on Science Interest and Achievement in Fourth-Grade Students: An Experimental Study in Ongka Malino District - Fahmi Abdul Rozak; Dasa Ismaimuza; Sandra Sukmaning Adji (AL-ISHLAH: Jurnal Pendidikan, 2026)
Elementary science instruction often remains teacher-centered, limiting student engagement and leading to suboptimal learning outcomes. This condition underscores the need for student-oriented approaches such as the Contextual Teaching and Learning (CTL) model, which connects scientific concepts to real-life contexts. This study aimed to examine the effect of CTL on fourth-grade students’ learning interest and academic achievement in science in the Ongka Malino District.A quantitative true experimental design with a pretest–posttest control group was employed. The sample consisted of 62 students from two elementary schools, divided into an experimental group receiving CTL-based instruction and a control group receiving conventional teaching. Data were collected using validated achievement tests and learning interest questionnaires and analyzed through paired sample t-tests.The findings revealed statistically significant improvements in both learning outcomes (t = 10.787, p 0.05) and learning interest (t = 11.575, p 0.05) among students in the experimental group. The effect sizes were large (Cohen’s d = 1.35 for achievement and d = 1.42 for interest), indicating a strong impact of the CTL model on both cognitive and affective domains.The results demonstrate that CTL is an effective instructional approach for enhancing students’ academic performance and engagement in science. By integrating real-life contexts into learning, CTL fosters meaningful understanding and intrinsic motivation. These findings support the adoption of context-based, active learning strategies to improve the quality of elementary science education.